2.2 Abnormal cerebroplacental ratio predicts adverse outcomes in dichorionic twins. (9th June 2014) - Kent, EM; Breathnach, FM; Burke, G; McAuliffe, FM; Geary, MP; Daly, S; Higgins, JR; Hunter, A; Morrison, JJ; Higgins, S; Mahony, R; Dicker, P; et al.
Abstract : Objective: To evaluate the significance of an abnormal cerebroplacental ratio (CPR) in twin pregnancies. Study design: In the prospective multicenter ESPRiT study, twin pregnancies underwent serial sonographic evaluation including multi-vessel Doppler studies. CPR was expressed as the ratio of the pulsatility index (PI) of the middle cerebral artery to the PI of the umbilical artery. CPR PI < 1.0 was considered abnormal. The relationship between abnormal CPR at final sonographic examination and adverse clinical outcomes was assessed and results stratified by chorionicity. A p-value of <0.01 was considered significant. Results: Of 1028 twin pairs recruited, 932 had CPR data available. 18% of the cohort were monochorionic (MC), of whom 15.2% had an abnormal CPR at the final sonographic evaluation. This was not significantly different among dichorionic (DC) twins (12.7%; p = 0.24 for comparison). In MC twins an abnormal CPR did not predict adverse clinical outcomes. In contrast, among DC twins an abnormal CPR prior to delivery was associated with reduced mean birthweight (BW) (p = 0.0002) and an increase in the rates of BW <5th centile (p = 0.01), NICU admission (p = 0.001) and perinatal morbidity (p = 0.002). There was also a trend toward a lower mean GA at delivery and higher rates of both preterm delivery and significant inter-twin BW discordance. Conclusion: An abnormal CPR is strongly associated with adverse outcomes in DC twin pregnancies but not in MC twin pregnancies. This reflects the differing pathological processes, which affect growth and placental function in DC and MC pregnancies.